Comparative analysis of the syncytiotrophoblast in placenta tissue and trophoblast organoids using snRNA sequencing - Madeline M Keenen; Liheng Yang; Huan Liang; Veronica J Farmer; Rizban E Worota; Rohit Singh; Amy S Gladfelter; Carolyn B Coyne (eLife)
The syncytiotrophoblast (STB) is a multinucleated cell layer that forms the outer surface of human chorionic villi. Its unusual structure, with billions of nuclei in a single cell, makes it difficult to resolve using conventional single-cell methods. To better understand STB differentiation, we performed single-nucleus and single-cell RNA sequencing on placental tissue and trophoblast organoids (TOs). Single-nucleus RNA-seq was essential for capturing STB populations, revealing three nuclear subtypes: a juvenile subtype co-expressing CTB and STB markers, one enriched in oxygen sensing genes, and another in transport and GTPase signaling. Organoids grown in suspension culture (STBout) showed higher expression of STB markers, hormones, and a greater proportion of the transport-associated nuclear subtype while TOs grown with an inverted polarity (STBin) exhibited a higher proportion of the oxygen sensing nuclear subtype. Gene regulatory analysis identified conserved STB markers, including the chromatin remodeler RYBP. Although RYBP knockout did not impair fusion, it downregulated CSH1 and upregulated oxygen-sensing genes. Comparing STB expression in first trimester, term, and TOs revealed shared features but context-dependent variability. These findings establish TOs as a robust platform to model STB differentiation and nuclear heterogeneity, providing insight into the regulatory networks that shape placental development and function.